Enhancing Brem Packaging at Suling Indah Jaya Madiun: A Quality Function Deployment (QFD) Application - Anjar Dwi Hastutik; Eka Bambang Gusminto; Cempaka Paramita; Vanya Pinkan Maridelana (Citakonsultindo, 2025)
Packaging plays a crucial role in attracting consumers and preserving product quality. Within the food industry, particularly for brem, innovative and functional packaging can enhance market competitiveness. This research employed the Quality Function Deployment (QFD) methodology to develop brem packaging at Suling Indah Jaya in Madiun, Indonesia. QFD was utilized to identify consumer needs and translate them into technical specifications to generate optimal packaging. Data were collected through customer questionnaires and interviews with company representatives. The House of Quality (HoQ) analysis generate five primary packaging attributes: product information, visual design, packaging functionality, form and size, and packaging material. The findings indicate that the product information aspect requires the most significant improvement, specifically concerning the halal label, logo, and composition details. The visual design focused on a combination of brown and white colors. Furthermore, the packaging should effectively protect the product from outdoor air, with an appropriate form and size. The materials utilized consist of plastic as the primary layer and cardboard for supplementary protection.